The phallocentric paradox and semantics of Eve"s myth in Zimbabwe"s contemporary national politics: An ecofeminist reading of Bulawayo"s novel, Glory - Mavengano, Esther (HTS teologiese studies, 2023)
NoViolet Bulawayo’s recently published novel titled, Glory, fictionalises the tragic fall of Robert Mugabe from the helm of power. The removal of Mugabe from power through the 2017 “military coup” engendered a problematic narrative that depicted the former first lady, Grace Mugabe as the biblical Eve’s doppelganger. The purported resemblance of Eve, a character from sacrosanct text, and Grace of contemporary Zimbabwe is often based on mythical and misogynist (mis)interpretations of the former as an epitome of sin and the latter as instrumental to Mugabe’s demise. Arguably, the construct of Eve in Zimbabwe and the personified allegory in the fictive society of Bulawayo is profoundly laden with semantics and tropes of power together interwoven with innuendoes that denigrate women. This article reflected upon the ‘blame Eve myth’ with interlocking discourses of toxic politics and religion that reinforce phallocentric attitudes and practices that denigrate the female gender in Zimbabwe. Ecofeminism enriches the discussions of the novel Glory as a satire that provides imperative fictional sites to chart these intricate discourses. Ecofeminist framework offers insights that enrich the discussions of Eve’s myth and other representations which disparage women in the novel, Glory. The study concludes that blaming Grace Mugabe in her fictional doppelganger Marvelous, symbolically illuminates how women and the feminised nature are both insulted and held accountable for woes that befall humanity in both the fictive nation of Jidada and its referent Zimbabwe.Contribution: Ecofeminist conceptual framework has rarely been used to examine the complex connection between gender, politics, religion and nature in Zimbabwean fictional writing. Thus, this study offered fresh insights that are significant in understanding these subjects from a multidisciplinary perspective because the analyses and readings of the novel were based on literary criticism, political discourse and theology.